Role of Religion: Implications of Personal Value and Corporate Culture on the Lecturer Job Satisfaction - ., Sundjoto; ., Kuswandi; Harjanti, Wulandari (Archives of Business Research, 2016)
The purpose this stud to examine the relationship between religion, corporate culture, personal values and lecturer job satisfaction in South Kalimantan. Data were obtained from a sample of 678 private college lecturer in South Kalimantan - Indonesia. There were five findings. First, religion does not influence the personal value. Second, corporate culture significantly influence personal value. Third, religion significantly influences lecturer job satisfaction. Fourth, corporate culture significantly influences lecturer job satisfaction and fifth, personal value significantly influences job satisfaction.